High-Density Lipoprotein Anti-Inflammatory Capacity and Incident Cardiovascular Events. Issue 20 (18th May 2021) - Jia, Congzhuo; Anderson, Josephine L.C.; Gruppen, Eke G.; Lei, Yu; Bakker, Stephan J.L.; Dullaart, Robin P.F.; Tietge, Uwe J.F.
Abstract : Background: The role of high-density lipoprotein (HDL) function in cardiovascular disease represents an important emerging concept. The present study investigated whether HDL anti-inflammatory capacity is prospectively associated with first cardiovascular events in the general population. Methods: HDL anti-inflammatory capacity was determined as its ability to suppress TNFα (tumor necrosis factor α)–induced VCAM-1 (vascular cell adhesion molecule-1) mRNA expression in endothelial cells in vitro (results expressed as achieved percent reduction by individual HDL related to the maximum TNFα effect with no HDL present). In a nested case-control design of the PREVEND (Prevention of Renal and Vascular End Stage Disease) study, 369 cases experiencing a first cardiovascular event (combined end point of death from cardiovascular causes, ischemic heart disease, nonfatal myocardial infarction, and coronary revascularization) during a median of 10.5 years of follow-up were identified and individually matched to 369 controls with respect to age, sex, smoking status, and HDL cholesterol. Baseline samples were available in 340 cases and 340 matched controls. Results: HDL anti-inflammatory capacity was not correlated with HDL cholesterol or hsCRP (high-sensitivity C-reactive protein). HDL anti-inflammatory capacity was significantly lower in cases compared with controls (31.6% [15.7–44.2] versus 27.0% [7.4–36.1]; P <0.001) and was inversely associated with incident CVD in a fully adjusted model (odds ratio [OR] per 1 SD, 0.74 [CI, 0.61–0.90]; P =0.002). Furthermore, this association was approximately similar with all individual components of the cardiovascular disease end point. The HDL anti-inflammatory was not correlated with cholesterol efflux capacity ( r =−0.02; P >0.05). When combining these 2 HDL function metrics in 1 model, both were significantly and independently associated with incident cardiovascular disease in a fully adjusted model (efflux: OR per 1 SD, 0.74; P =0.002; anti-inflammatory capacity: OR per 1 SD, 0.66; P <0.001). Adding HDL anti-inflammatory capacity improved risk prediction by the Framingham risk score, with a model likelihood-ratio statistic increase from 10.50 to 20.40 ( P =0.002). Conclusions: The HDL anti-inflammatory capacity, reflecting vascular protection against key steps in atherogenesis, was inversely associated with incident cardiovascular events in a general population cohort, independent of HDL cholesterol and HDL cholesterol efflux capacity. Adding HDL anti-inflammatory capacity to the Framingham risk score improves risk prediction. Abstract : Supplemental Digital Content is available in the text.